Analisis Penerapan Prinsip Kehati-Hatian (Prudential Principle) Dalam Penyaluran Pembiayaan Konsumtif Pada Lembaga Keuangan Syariah - Nawa, Maulin; Andriyanto , Irsyad (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2024)
The aim of this research is to explain the application of the prudential principle in the distribution of consumer financing at DI BMT MUBARAKAH KUDUS. The type of research that the author conducted was field research with a qualitative descriptive approach. This research was carried out at BMT Mubarakah Kudus. The subjects of this research were managers, tellers, marketing and customers of BMT Mubarakah Kudus. The main data sources obtained directly from the original sources through observation, interviews, or surveys, and secondary data sources come from relevant literature studies. The data collection techniques in this research are interviews and documentation. Meanwhile, testing the validity of the data through triangulation of methods, theories and data sources. The data analysis technique is applied using an inductive thinking approach to examine in depth the analysis of the application of the prudential principle in the distribution of consumer financing at BlMT Mubarakah Kudus. The results of the research show that the application of the prudential principle in consumer financing at BMT Mubarakah Kudus applies a feasibility analysis based on the 6 C principles (character, capacity, capital, condition, collateral and constraints) with an emphasis on the analysis aspects of character, ability, and guarantee. The factors that influence the occurrence of problematic consumer financing involve internal aspects, where BMT Mubarakah Kudus faces a lack of caution in analyzing prospective customers when applying for financing. Meanwhile, external factors, including economic conditions that have not fully recovered after the pandemic, have caused a decline in income for many businesses.